2021
DOI: 10.3390/agriculture11040325
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Irrigation Interval after Anthesis on Grain Quality, Alkali Digestion, and Gel Consistency of Rice

Abstract: The management of amylose and protein contents and cooking quality are the main challenges in rice macronutrients and quality improvement. This experiment was conducted to examine the rice grain quality, alkali digestion, and gel consistency responses to irrigation interval after anthesis. Three rice varieties (K1, K3, and K4) were subjected to different irrigation intervals (1, 2, and 3 d) after anthesis. The findings of this study showed that the protein content was markedly increased from 6.53–6.63% to 9.93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In general water deficit treatment significantly reduced hulling %, milling %, head rice %, amylose content %, gelatinization temperature and grain shape. These results confirm that reported by Rayee et al, (2021). The interaction between genotypes, environments (normal and water deficit conditions) and seasons are shown in Table 7.…”
Section: Interaction Effectssupporting
confidence: 91%
“…In general water deficit treatment significantly reduced hulling %, milling %, head rice %, amylose content %, gelatinization temperature and grain shape. These results confirm that reported by Rayee et al, (2021). The interaction between genotypes, environments (normal and water deficit conditions) and seasons are shown in Table 7.…”
Section: Interaction Effectssupporting
confidence: 91%
“…Ample evidence found that the qualitative characters of white rice were closely related to gel consistency, chalkiness rice rate, contents of protein, total starch, and amylose contents [4]. Subsequent results discovered that compare to the control group (83.1 ± 2.4 mm), HNW could increase the gel consistency to 91.4 ± 3.4 mm (Figure 5A), a relatively perfect support for higher quality of eaten rice [34]. Strikingly, the chalkiness rate of rice was obviously decreased by HNW (Figure 5B).…”
Section: Qualitative Characters Of White Rice Irrigated With Hnwmentioning
confidence: 92%
“…The final grain yield at 14% of the moisture was then calculated based on the weight and the determined moisture. The gel consistency of the rice grains was determined according to the method illustrated by Rayee et al (2021). The grain protein content was calculated by multiplying grain N content with 5.95 (Yasui and Tsutsumi, 1982).…”
Section: Discussionmentioning
confidence: 99%